Diseño y desarrollo de una aplicacion movil para dispositivos android para un sistema de alerta temprana de los arroyos de la ciudad de Barranquilla (2014)
The Project development presents the creation of a mobile application for Android OS using the technology of Google Maps Api, under the concept of MVC design pattern (Model – View - Controller) and programming methodology cascade, which it is supported on development phases like requirements definition, software design, implementation and unit testing, system integration testing and operation and maintenance. The goal of this application is present graphically to the citizens who install the application on their mobile devices, the routes of certain streams which are present in the city of Barranquilla as well as sending preventive alerts to the devices, about situations of high-risk that may occur by high stream flow. The results of the project are the realization of an application that look for generating through giving of information to users, prevention with respect to streams that are generated in different parts of the city and the knowledge technical, theoretical and even historical that were acquired during development, that give you an idea to reflection about how complex is the problem that the city has been suffering from its beginnings.